原料压榨制油的预处理方式对核桃多肽功能特性 和ACE抑制活性的影响Effect of raw material pretreatment method in oil pressing on functional characteristics and ACE inhibitory activity of walnut polypeptide - 高盼1,2，韩玉博1，杨永2，马开创1，钟武1,2，胡传荣1， 何东平1,2，张晖3，张跃进4，王兴国1,3 GAO Pan1,2, HAN Yubo1, YANG Yong2, MA Kaichuang1, ZHONG Wu1,2, HU Chuanrong1, HE Dongping1,2, ZHANG Hui3, ZHANG Yuejin4, WANG Xingguo1,3 (Zhongguo youzhi, 2023)
旨在研究原料压榨制油的预处理方式对核桃多肽性质的影响。对核桃仁分别进行未预处理、去衣、焙烤预处理后，进行压榨提油，以提油后的饼为原料，经正己烷脱脂，碱性蛋白酶酶解制备核桃多肽，测定核桃多肽的功能特性和ACE抑制活性。结果表明：与未预处理、焙烤预处理比较，去衣预处理的核桃多肽的持水性(50 ℃，5.11 g/g)、吸油性(50 ℃，3.25 g/g)、乳化性(pH 9.0,6257%)、乳化稳定性(pH 9.0,84.51%)、起泡性(pH 9.0,117.49%)及ACE抑制率（63.04%）最高。综上，以去衣预处理压榨制油后的核桃饼为原料制备的核桃多肽具有良好的功能特性和ACE抑制活性。The aim was to study the effect of pretreatment methods of raw material pressing for oil on the properties of walnut polypeptide. The walnut kernels were untreated, peeled and roasted respectively,then pressed to extract oil.The cake after oil extraction was defatted by n-hexane and hydrolyzed by alkaline protease to produce walnut polypeptide, and the functional properties and ACE inhibitory activity of walnut polypeptide were determined. The results showed that compared with no treatment and roasting pretreatment, walnut polypeptide obtained by peeling of raw material had the highest water holding capacity (50 ℃, 5.11 g/g), oil absorption (50 ℃,3.25 g/g), emulsifying ability (pH 9.0, 62.57%), emulsifying stability (pH 9.0, 84.51%), foaming ability (pH 9.0, 117.49%) and ACE inhibitory rate( 63.04%). In conclusion, the walnut polypeptide prepared from walnut cake after peeling and pressing for oil production had good functional properties and ACE inhibitory activity.